Pertanggungjawaban Hukum Calon Notaris dalam Menjaga Kerahasiaan Pembuatan Akta dalam Optik Kepastian Hukum - Khemal Akbar, Moh.; Rasji, Rasji (Universitas Ekasakti, 2023)
In functional subjectivity in law, a person who is a notary in criminal or civil and administrative matters due to the impact of not being able to maintain the confidentiality of the making of a deed can be associated through laws that are related to preventive legal protection for notaries. The aim of writing this scientific work is to analyze legal accountability. notary candidates in maintaining the confidentiality of deed making in the optics of legal certainty. The research method used is the Normative Juridical method, with a statutory and conceptual approach. The types of legal materials are primary, secondary and tertiary using literature study techniques to search for legal materials. Analysis techniques for systematic interpretation of legal materials. The results obtained are efforts to protect the legal liability of prospective notaries in maintaining confidentiality making deeds in the optics of legal certainty contained in preventive law which has 2 (two) aspects, namely the internal aspect preventive legal protection in the form of considering worker qualifications, increasing supervision, making work agreements and repression. On the side externally, there are special provisions in the UUJN regarding the position of workers as an instrument witness. Repressive legal protection in the form of filing criminal cases and civil lawsuits. The existence of repressive efforts constitutes mitigation efforts, meaning that these efforts are emphasized more in the event of a lossborne by the Notary